Pengetahuan Dan Sikap Masyarakat Tentang Gastritis Di Puskesmas Dolo Kecamatan Dolo Kabupaten Sigi - Adikari Sekeon, Robi; Tarigan, Sabarulin; Anggreani Madude, Meilin (BULLET : Jurnal Multidisiplin Ilmu, 2024)
Gastritis is inflammation (swelling) of the gastric mucosa characterized by discomfort in the upper stomach, nausea, vomiting, decreased appetite or headaches. According to the results of a preliminary study, data that researchers obtained from the Dolo Community Health Center showed that the number of gastritis sufferers in 2018 was 2119 cases. The aim of this research is to determine the knowledge and attitudes of the community about gastritis at the Dolo Community Health Center, Dolo District, Sigi Regency. The design of this research is descriptive research. The variables in this research are people's knowledge and attitudes. The data used is primary and secondary data. Data analysis uses univariate analysis. The population in this study were people who visited the community health center at the time of the research. The sample in this study amounted to 43 people using the Accidental Sampling method. The research results showed that respondents who had good knowledge about Gastritis were 69.8% and 30.2% were sufficient, while those who had good attitudes were 51.2% and 48.8% were sufficient. The conclusion in this research is that the samples obtained during the research had more good knowledge and good attitudes about gastritis. Suggestions: It is hoped that the Dolo Community Health Center can work together with the Subdistrict/Village Government to socialize and provide education about health, especially related to gastritis so that people can further improve their knowledge and attitudes about gastritis.